Activities in the space that formalizes social responsibility from the perspective of completed research - Kapias, Michał; Polok, Grzegorz (Annales. Etyka w Życiu Gospodarczym, 2019)
Lately, the subject of responsibility has gained importance in the context of the economic crisis. In economy, it took the form of social responsibility. It concerns activities additionally undertaken by organizations in order to establish correct relations with their employees and society, as well as with regard to the natural environment. Therefore, a very important role is played by the ethos of the undertaken socially responsible actions. To a large extent, it is reflected in the ethical dimension. Thus, in enterprises, codes of ethics have become a base of axiology in the building of the organizational cultures. Unfortunately, Polish companies—as shown in the paper—still attach a lesser role to the ethical dimension of business.